The cosmopolitan imagination : the renewal of critical social theory - Delanty, Gerard (Cambridge : Cambridge University Press, 2009)
Gerard Delanty provides a comprehensive assessment of the idea of cosmopolitanism in social and political thought which links cosmopolitan theory with critical social theory. He argues that cosmopolitanism has a critical dimension which offers a solution to one of the weaknesses in the critical theory tradition: failure to respond to the challenges of globalization and intercultural communication. Critical cosmopolitanism, he proposes, is an approach that is not only relevant to social scientific analysis but also normatively grounded in a critical attitude. Delanty's argument for a critical, sociologically oriented cosmopolitanism aims to avoid, on the one hand, purely normative conceptions of cosmopolitanism and, on the other, approaches that reduce cosmopolitanism to the empirical expression of diversity. He attempts to take cosmopolitan theory beyond the largely Western context with which it has generally been associated, claiming that cosmopolitan analysis must now take into account non-Western expressions of cosmopolitanism.
The rise and decline of classical cosmopolitanism -- Contemporary cosmopolitanism and social theory -- Global ethics, solidarity and the problem of violence -- Cosmopolitan citizenship and the post-sovereign state -- Multiculturalism from a cosmopolitan perspective -- Religion in a cosmopolitan society -- Cosmopolitanism, modernity and global history -- Cosmopolitanism and European political community -- Europe as a borderland -- Conclusion : inter-cultural dialogue in a post-Western world.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Critical theory; Cosmopolitanism